Urgensi Pencabutan Hak Asuh Anak dalam Kasus Kekerasan terhadap Anak di Indonesia - Fauziyah, Diana; Setyorini, Hening Hapsari (Wajah Hukum, 2025)
Child Custody can be given to a parent in accordance with the best interest of the child. In reality, many parents who hold child custody do not do their responsibility in caring for and protecting their child well. This reality leads to many child abuse cases and even the death of the child. This research aims to examine should the child custody is revoked in some cases discussed in this research and how the parent who does not hold child custody can supervise child custody. This research was conducted using doctrinal research method which used the secondary data as a primary data to answer the problem. The answer of the problem is that the revocation of child custody is needed if the parent who holds child custody do not fulfill responsibility to her or his child as regulated in Article 49 of The Marriage Law. The parent who does not hold child custody can supervise child custody with visitation right. Unfortunately, there is no explicit regulation regarding this right.